The Personality: KEPRIBADIAN TOKOH HIRO DALAM FILM KOZORA OLEH NATSUKI IMAI - Da Cunha, Anastasia Erin; Made Henra Dwikarmawan Sudipa (Program Studi Sastra Jepang Fakultas Bahasa Asing Unmas Denpasar, 2023)
The purpose of this research is to analyze the personality of the main male character, Hiro in the drama of Koizora. The data source used in this study is a romantic love story drama entitled Koizora or in English called Sky Of Love. Using the theory of personality by Sigmund Freud (In Minderop, 2011:21-22) is divided into three parts of personality structure namely id, ego, and super-ego. Based on the analysis of Koizora drama, the results show that the more dominant personality in Hiro is the id. This can be seen from Hiro’s actions at the beginning of the episode.